Pelvic Organ Motion during Radiotherapy for Cervical Cancer: Understanding Patterns and Recommended Patient Preparation. Issue 9 (September 2016) - Eminowicz, G.; Motlib, J.; Khan, S.; Perna, C.; McCormack, M.
Abstract: Aims: Minimisation of organ position variation during pelvic radiotherapy is vital for accurate treatment. We analysed bladder and rectal filling during radiotherapy to understand variation reduction methods. Materials and methods: Cone beam computed tomography scans (CBCTs) taken twice weekly during three-dimensional conformal radiotherapy were retrospectively analysed for 10 cervical cancer patients. Bladder and bowel preparation was followed. Two independent clinicians outlined bladder, rectum and the primary clinical target volume (CTV) on each CBCT. Effects of time, chemotherapy and drinking time on bladder and rectal volume were analysed. CTV coverage impact was investigated using fixed effect logistic regression modelling. Results: Ten planning scans and 109 CBCTs were reviewed. The bladder volume was 45–578 cm 3 during radiotherapy and 73–664 cm 3 at planning. The bladder volume increased (4 cm 3 /min) with waiting time, decreased (average 4 cm 3 /day) through treatment and was larger (about 50 cm 3 ) after chemotherapy. A bladder volume difference > 130 cm 3 from planning led to the planning target volume (PTV) not covering the CTV. The probability of the PTV covering the CTV for every cm 3 deviation from the planning volume reduced by 1.9%, predominantly affecting the uterus. Planning bladder volumes > 300 cm 3 were not reproducible during treatment. The rectal anterior-posterior diameter correlated with volume. No pattern was displayed through treatment. The probability of the PTV covering the CTV with every mm deviation from the planning anterior-posterior diameter reduced by 5.8%, predominantly affecting the cervix. The risk of the PTV not covering the CTV is higher if the rectum is larger during treatment than planning. As bladder volume decreased rectal anterior-posterior diameter increased. Conclusion: Our data suggest an ideal planning bladder volume of 150–300 cm 3, a shorter waiting time on post-chemotherapy days and adequate hydration throughout treatment. Laxatives at planning and throughout treatment may also be beneficial. Even with these measures, regular imaging is vital when implementing advanced radiotherapy techniques for gynaecological cancers. Highlights: Bladder and rectal filling during chemoradiation are variable despite protocol. Bladder volume > 300 cm 3 at planning is not reproducible. Bladder volume deviation > 130 cm 3 from planning leads to CTV outside the PTV. Bladder volume is larger on post-chemotherapy days. Patient preparation protocol proposed with bladder range 150–300 cm 3 .